Wait-and-Follow: Tourism Policies Amid The Early Widespread of Covid-19 within The Special Region of Yogyakarta - Hapsari, Riris Rinonce (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2023)
An unforeseen repercussion of the COVID-19 pandemic was a substantial disruption of international economic activity. Similarly affected was the Special Region of Yogyakarta, one of the most visited tourist havens in Indonesia. Initial policies implemented in the midst of the pandemic were pivotal in assessing the government's readiness to address unanticipated circumstances. In addition to disseminating a wide range of information and ideas, mass media functions as a vital social institution by monitoring the political climate and the effectiveness of the government. By employing Fairclough's critical discourse analysis, it is possible to ascertain the relation between public policy and mass media. Therefore, the objective of this study is to examine how the news media, particularly Tribun Jogja, communicated the tourism policies of the Special Region of Yogyakarta concurrently with the early phases of the COVID-19 pandemic (January-June 2020). During the whole of the investigation, it was critical to partition the data into distinct time intervals in order to draw verdicts. As a result of the prevailing circumstances, Tribun Jogja was convened to deliberate on the tourism policies enacted by the administration of the Yogyakarta Special Region. Furthermore, it was disclosed that the previously mentioned organisations were participating in collaborative initiatives.